Actively Q-switched and modelocked all-fiber lasers - Cuadrado Laborde, Christian Ariel (2010)
Here we demonstrate active mode-locking (ML) and doubly-active Q-switching mode-locking (QML) of erbium doped strictly all-fiber lasers. The active ML mechanism relies in the acoustooptic superlattice modulation (AOSLM) effect induced when longitudinal acoustic waves are launched along a fiber Bragg grating. In both regimes - ML as well as QML - we focus on the laser behavior when the AOSLM is driven by traveling acoustic waves, and next we compare these results with those obtained when the AOSLM is driven by standing acoustic waves. In the ML regime, optical pulses were obtained of 530 mW peak power, 700 ps temporal width, at a repetition rate of 4.1 MHz. On the other hand, in the QML regime, the laser generates trains between 10 – 25 modelocked pulses around 700 ps each, within a Q-switched envelope of about 1 – 3 micro-s, and a maximum overall energy of 0.68 micro-J.